2013
DOI: 10.11634/216796061302247
|View full text |Cite
|
Sign up to set email alerts
|

A Diagnostic Method for Procedural Justice

Abstract: Procedural justice has shown significant linkages to organizational outcomes such as organizational commitment and turnover. For this reason, we propose that measures of procedural justice can serve a diagnostic function to signal potential problems with important organizational-level outcomes. However, if used alone, it does not tell us which specific procedures require change in order to resolve potential problems. This study proposes, and tests, a methodology which combines general measures of procedural ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…In this study, the outcome will be rejection or offer given by either the human decision-maker or by the AI decision-making system. These above-mentioned justice components have been well researched including procedural justice , distributive justice (Pan, Chen, Hao, & Bi, 2018;Flint, & Haley, 2013;Smither et al, 1993), interpersonal justice (McNall, & Roch, 2007;Ryan & Chan, 1999), informational justice (Cheung, 2013;. A meta-analysis by Hausknecht et al, (2004) demonstrated the unique contribution of each type of the four types of justice explored above to commonly studied applicant reactions variables (e.g., job acceptance, recommending a friend).…”
Section: Ai and Justice Perceptionsmentioning
confidence: 99%
“…In this study, the outcome will be rejection or offer given by either the human decision-maker or by the AI decision-making system. These above-mentioned justice components have been well researched including procedural justice , distributive justice (Pan, Chen, Hao, & Bi, 2018;Flint, & Haley, 2013;Smither et al, 1993), interpersonal justice (McNall, & Roch, 2007;Ryan & Chan, 1999), informational justice (Cheung, 2013;. A meta-analysis by Hausknecht et al, (2004) demonstrated the unique contribution of each type of the four types of justice explored above to commonly studied applicant reactions variables (e.g., job acceptance, recommending a friend).…”
Section: Ai and Justice Perceptionsmentioning
confidence: 99%
“…Researchers have conceptualized OJ as a function of three separate variables: distributive, procedural and interactional justice (Chan and Lai, 2017; Elamin and Tlaiss, 2015; Alzayed et al, 2017; Karriker and Williams, 2009). Procedural justice refers to the employees’ perceptions of fairness in terms of procedures that are adapted to deliver the outcome decisions (Flint et al, 2013). Specifically, the integrity of the procedures must involve the degree of equity in the processes used to formulate decisions (Lopez-Cabarcos et al, 2015) and the extent to which employees are allowed to give voice to their positions before making any decision (Flint et al, 2013) based on accurate information and ethical standards (Pan et al, 2018).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Procedural justice refers to the employees’ perceptions of fairness in terms of procedures that are adapted to deliver the outcome decisions (Flint et al, 2013). Specifically, the integrity of the procedures must involve the degree of equity in the processes used to formulate decisions (Lopez-Cabarcos et al, 2015) and the extent to which employees are allowed to give voice to their positions before making any decision (Flint et al, 2013) based on accurate information and ethical standards (Pan et al, 2018). In this study, procedural justice is the employees’ perception that the procedures by which decisions are made by the management are fair, well explained and implied equally, while interactional justice meets the four communication criteria: truthfulness, justification, honour and fitness.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%